Epigenetic reprogramming of cancer cells under embryonic microenvironment - Mu, X.; Sultankulov, B.; Agarwal, R.; Mahjoub, A.; Schott, T.; Greco, N.; Huard, J.; Weiss, K. (Nazarbayev University, 2014)
The idea of epigenetic reprogramming of cancer cells by an embryonic microenvironment possesses potential interest from the prospect of both basic science and potential therapeutic strategies. Chick embryo extract (CEE) has been used for the successful expansion of many specific stem cells and has demonstrated the ability to facilitate DNA demethylation. The current study was conducted to compare the status of DNA methylation in highly metastatic and less metastatic osteosarcoma cells and to investigate whether CEE may affect the epigenetic regulation of tumor suppressor genes and thus change the metastatic phenotypes of highly metastatic osteosarcoma cells.
Keywords: epigenetic reprogramming; embryonic microenvironment; osteosarcoma cells; cell apoptosis; genes